2019
DOI: 10.1097/jxx.0000000000000105
|View full text |Cite
|
Sign up to set email alerts
|

A model of successful DNP and PhD collaboration

Abstract: Background and purpose: Within nursing education, the existence of two graduate-level programs has created some challenges. Role confusion between the practice-focused Doctor of Nursing Practice (DNP) and the research-focused Doctor of Philosophy (PhD) is compounded by competition for similar positions. Collaboration between DNP and PhD nurses, however, benefits the health care system and patients. Methods: The complementary skills of these two groups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…Faculty perspectives were consistent with a number of positive themes emerging, including mutual respect, positive leadership, empowerment, and equity. These themes are consistent with the literature regarding determinants for successful workplace collaboration, team-based decision making, and a healthy academic culture [10,15,17]. Shared governance, team-based curriculum development, and a hybrid mentoring model are all interventions used to promoted collaboration.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Faculty perspectives were consistent with a number of positive themes emerging, including mutual respect, positive leadership, empowerment, and equity. These themes are consistent with the literature regarding determinants for successful workplace collaboration, team-based decision making, and a healthy academic culture [10,15,17]. Shared governance, team-based curriculum development, and a hybrid mentoring model are all interventions used to promoted collaboration.…”
Section: Discussionsupporting
confidence: 81%
“…Shared governance, team-based curriculum development, and a hybrid mentoring model are all interventions used to promoted collaboration. Intentional collaboration of faculty is viewed as one of the most successful tools in the overall healthy work environment and in the team approach [15]. Overall, the faculty who participated in the study reported an academic culture that promoted civility, inclusivity, and collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…There are inherent strengths within collaborations among research‐ and practice‐based doctoral nurses for both implementation and potential de‐implementation of practices in clinical settings (Cowan, Hartjes, & Munro, 2019). Among nurse scientists, their strengths include the ability to effectively design and conduct research, build programs of research, generate evidence to guide practice, and disseminate findings through scientific publications and presentations (Cowan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…There are inherent strengths within collaborations among research‐ and practice‐based doctoral nurses for both implementation and potential de‐implementation of practices in clinical settings (Cowan, Hartjes, & Munro, 2019). Among nurse scientists, their strengths include the ability to effectively design and conduct research, build programs of research, generate evidence to guide practice, and disseminate findings through scientific publications and presentations (Cowan et al, 2019). For DNP and practice‐based doctoral nurses, their strengths include the ability to lead and implement practice changes, manage and reduce resistance to change, design and interpret quality improvement initiatives, serve as clinical experts, interpret and translate evidence into local practice settings, and disseminate efforts through professional practice channels, clinical presentations, and publications (Cowan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, nurse scientists must be able to build relationships throughout the organization to garner support of key stakeholders and leaders. Melnyk et al (2017) Therefore, a partnership might facilitate success and sustainability (Cowan et al, 2019;McNett et al, 2021) when establishing a nurse scientist role within an organization.…”
Section: Discussionmentioning
confidence: 99%